2020
DOI: 10.1002/jum.15213
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Ultrasound and Doppler Features of Intraligamental Myomas

Abstract: ObjectivesTo describe the ultrasound (US) features of intraligamental myomas (IMs) using Morphological Uterus Sonographic Assessment group standardized terminology.MethodsThis was a retrospective monocentric study. A total of 125 consecutive women with a preoperative US diagnosis of a myoma located close to the uterine isthmus (International Federation of Gynecology and Obstetrics stages 5, 6, and 7) from 2016 to 2019 who underwent laparoscopic or laparotomic myomectomy or hysterectomy were included for study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…26 A review of the literature showed that the uterus, the tumor corresponds to a broad ligament leiomyoma. 3,27 Ultrasound in most reported cases of the literature review showed heterogeneous mass with multiple septations. Characteristic performance is difficult to detect because of the degeneration and necrosis of leiomyoma, resulting a dilemma in diagnosis, and the misdiagnosis rate can reach 12%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…26 A review of the literature showed that the uterus, the tumor corresponds to a broad ligament leiomyoma. 3,27 Ultrasound in most reported cases of the literature review showed heterogeneous mass with multiple septations. Characteristic performance is difficult to detect because of the degeneration and necrosis of leiomyoma, resulting a dilemma in diagnosis, and the misdiagnosis rate can reach 12%.…”
Section: Discussionmentioning
confidence: 97%
“…Transverse blood flow is its characteristic performance. If the detected vascular pedicle is attached to the uterus, the tumor corresponds to a broad ligament leiomyoma 3,27 . Ultrasound in most reported cases of the literature review showed heterogeneous mass with multiple septations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the non-imaging of the right ovary was incorrectly not attributed to its elevation due to the displacement of the suspensory ligament by the presence of the huge intraligamental leiomyoma. Based on the experience from the management of patients with large intraligamental leiomyomas, it is considered that the determination and awareness of specific imaging features of these tumors may assist in the accurate preoperative diagnosis, which allows for the planning of the optimal surgical treatment and the avoidance of severe intraoperative and/or post-operative complications ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 89% of these myomas showed increased flow within the tumor (MUSA grade 3 or 4), compared with the control group. Interligamentous myomas were solid in 84% of cases (34) .…”
Section: Imaging Diagnosis Of Uterine Myomasmentioning
confidence: 96%